2007
DOI: 10.1038/ismej.2007.98
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal diversity analysis of spacecraft assembly clean rooms

Abstract: One of the main tasks of NASA's planetary protection program is to prevent the forward contamination of extraterrestrial environments with Earth life, and in turn preserve other planets and the integrity of future life detection missions. Despite information regarding bacterial diversity in NASA's clean rooms, little is known about the presence of Archaea. Archaeal community analysis of spacecraft-associated surfaces is important, as they are considered by some to represent terrestrial life most capable of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 18 publications
(16 reference statements)
1
50
0
Order By: Relevance
“…The majority of sequences obtained, clustered with mainly uncultivated Crenarchaeota from very diverse biotopes like soil, sediments, deserts or plant roots (Figure 1). Interestingly, the US American clean room sequences (Moissl et al, 2008) clustered within this group of Archaea as well (crenarchaeal soil group 1b; DeLong, 1998), and were closely related to the newly retrieved clone Archaea in global spacecraft assembly clean rooms C Moissl-Eichinger sequences. The closest cultivated neighbor to these sequences was the thermophilic ammonia oxidizer candidatus Nitrososphaera gargensis (Hatzenpichler et al, 2008), showing up to 96% similarity in the 16S rRNA gene with the sequences from this study.…”
Section: Archaea In Global Spacecraft Assembly Clean Rooms C Moissl-ementioning
confidence: 99%
See 4 more Smart Citations
“…The majority of sequences obtained, clustered with mainly uncultivated Crenarchaeota from very diverse biotopes like soil, sediments, deserts or plant roots (Figure 1). Interestingly, the US American clean room sequences (Moissl et al, 2008) clustered within this group of Archaea as well (crenarchaeal soil group 1b; DeLong, 1998), and were closely related to the newly retrieved clone Archaea in global spacecraft assembly clean rooms C Moissl-Eichinger sequences. The closest cultivated neighbor to these sequences was the thermophilic ammonia oxidizer candidatus Nitrososphaera gargensis (Hatzenpichler et al, 2008), showing up to 96% similarity in the 16S rRNA gene with the sequences from this study.…”
Section: Archaea In Global Spacecraft Assembly Clean Rooms C Moissl-ementioning
confidence: 99%
“…A previous study showed that because of low microbial biomass observed in spacecraft-assembly clean rooms, and the even lower abundance of Archaea, parallel samples taken in one clean room led to 2/3 negative results when screened for archaeal 16S rRNA genes (Moissl et al, 2008). Therefore, samples from larger surface areas were taken and pooled in order to detect archaeal signatures more effectively.…”
Section: Archaea In Global Spacecraft Assembly Clean Rooms C Moissl-ementioning
confidence: 99%
See 3 more Smart Citations